Tiger prowling: Distribution modelling for northward-expanding Aedes albopictus (Diptera: Culicidae) in Japan - Yang, Chao; Futami, Kyoko; Nihei, Naoko; Fujita, Ryosuke; Ogino, Kazumasa; Hirabayashi, Kimio; Yonejima, Mayuko; Otsuka, Yasushi; Nakamura, Satoshi; Taira, Kensuke; Owhashi, Makoto; Motoki, Mitsugu; et al. (PloS one, 2024)
The Asian tiger mosquito, Aedes albopictus , is a significant public health concern owing to its expanding habitat and vector competence. Disease outbreaks attributed to this species have been reported in areas under its invasion, and its northward expansion in Japan has caused concern because of the potential for dengue virus infection in newly populated areas. Accurate prediction of Ae . albopictus distribution is crucial to prevent the spread of the disease. However, limited studies have focused on the prediction of Ae . albopictus distribution in Japan. Herein, we used the random forest model, a machine learning approach, to predict the current and potential future habitat ranges of Ae . albopictus in Japan. The model revealed that these mosquitoes prefer urban areas over forests in Japan on the current map. Under predictions for the future, the species will expand its range to the surrounding areas and eventually reach many areas of northeastern Kanto, Tohoku District, and Hokkaido, with a few variations in different scenarios. However, the affected human population is predicted to decrease owing to the declining birth rate. Anthropogenic and climatic factors contribute to range expansion, and urban size and population have profound impacts. This prediction map can guide responses to the introduction of this species in new areas, advance the spatial knowledge of diseases vectored by it, and mitigate the possible disease burden. To our knowledge, this is the first distribution-modelling prediction for Ae . albopictus with a focus on Japan.